ACCOUNTING POLICY: ESSENCE AND IMPACT OF EXTERNAL AND INTERNAL FACTORS ON FORMATION AND PRACTICE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The study is dedicated to exploring the essence of accounting policy of an enterprise and analyzing theinfluence of internal and external factors on its formation and practical application. Accounting policy plays a crucialrole for economic entities, as it determines the proper organization of accounting based on which financial statementsare prepared and managerial decisions are made. It is the accounting policy that structures information and establishesa set of actions for the accounting representation of business processes. The structure of accounting policy, in turn,depends on the type of activities of the economic entity, production or trading technologies, organizational status, andsize.The study examines internal factors such as organizational and legal form, scale of operations, production andorganizational structure, information provision, personnel qualifications, and other aspects of internal enterpriseactivities that influence accounting policy. External factors are also analyzed, including regulatory and legalregulations, industry-specific considerations, taxation system, market infrastructure, and other external conditions thatsignificantly impact the formation and practice of accounting policy.A comprehensive approach to the formation of accounting policy, which involves analyzing internal and externalfactors, enables the development of an effective strategy to achieve set objectives and adapt accounting policy tochanges in the internal and external environment. Considering all relevant factors and properly shaping accountingpolicy will contribute to optimal accounting management, control over financial resources, and timely managerialdecision-making within the enterprise.The main objective of the research is to identify various approaches to defining accounting policy proposed byauthors from different sources and to analyze the impact of factors on the formation of the enterprise's accountingpolicy.The research holds practical significance for enterprises aiming to enhance the effectiveness of their accountingpolicy and adapt to changes in the internal and external environment. It is also relevant for researchers and studentsexploring issues related to accounting and enterprise management.
Keywords: accounting policy, enterprise, financial accounting, managerial accounting, tax accounting, external and internal factors.